Play Counseling Approach in Overcoming Academic Anxiety among Lower Grade Elementary School Students - Rusmiani, Dewi; Maulana, Ade Hilman (Jurnal Ar Ro'is Mandalika (Armada), 2025)
Academic anxiety is a common challenge for lower-grade elementary school students, often triggered by academic tasks, examinations, or teacher evaluations. Such anxiety can diminish concentration, reduce motivation, and hinder academic performance if left unaddressed. To address this issue, schools require interventions that are developmentally appropriate and effective. One promising approach is play counseling, which utilizes play as a natural medium for children to express feelings, confront fears, and develop coping strategies in a safe environment. This study aims to explore the effectiveness of structured play counseling in reducing academic anxiety while enhancing students’ motivation and self-confidence. A qualitative literature review method was employed, drawing upon academic articles, reports, and publications from 2015–2025 obtained through reputable databases including Google Scholar, ScienceDirect, PubMed, and SpringerLink. Articles focusing on play therapy, counseling, and academic anxiety among elementary school children were systematically analyzed using thematic analysis. The findings indicate that play counseling, particularly through non-directive play, cognitive-behavioral play therapy (CBPT), and child-centered play therapy (CCPT), significantly reduces academic anxiety by providing children with a safe medium for symbolic expression. Moreover, play counseling fosters motivation and builds academic self-confidence by reframing learning as enjoyable exploration rather than stressful evaluation. Case studies demonstrate improvements in classroom participation, test-taking resilience, and peer interaction. These results highlight play counseling as an effective psychosocial intervention that supports both emotional well-being and academic outcomes for young learners. The study contributes to developing adaptive play-based counseling strategies suitable for Indonesian elementary school settings.